The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s11164-022-04839-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and pesticidal activity of new 1,3,4-oxadiazole thioether compounds containing a trifluoromethylpyrazoyl moiety

Abstract: In order to find new lead compounds with high pesticidal activity, a series of 1,3,4-oxadiazole thioether compounds ( 5 series) were designed by using penthiopyrad as a synthon. They were synthesized easily via five steps by using ethyl 4,4,4-trifluoro-3-oxobutanoate and triethyl orthoformate as starting materials. The synthesized compounds were characterized by 1 H NMR, 13 C NMR and HRMS. The compound 2-(benzylthio)-5-(1-methyl-3-(trifluorom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Shi et al. (2022) synthesized 2‐((3‐chlorobenzyl) thio)‐5‐(1‐methyl‐3‐(trifluoromethyl)‐1H‐pyrazol‐5‐yl)‐1,3,4‐oxadiazole 139 and 2‐((4‐bromobenzyl) thio)‐5‐(1‐methyl‐3‐(trifluoromethyl)‐1H‐pyrazol‐5‐yl)‐1,3,4‐oxadiazole 140 which were showing herbicidal activity. Compound 139 were found phytotoxicity against lettuce ( Lactuca sativa ) and bentgrass ( Agrostis stolonifera ) at 1 mM and compound 140 found the bleaching effect phenomenon against bentgrass at 1 mM.
…”
Section: Applications Of 134‐oxadiazolesmentioning
confidence: 99%
“…Shi et al. (2022) synthesized 2‐((3‐chlorobenzyl) thio)‐5‐(1‐methyl‐3‐(trifluoromethyl)‐1H‐pyrazol‐5‐yl)‐1,3,4‐oxadiazole 139 and 2‐((4‐bromobenzyl) thio)‐5‐(1‐methyl‐3‐(trifluoromethyl)‐1H‐pyrazol‐5‐yl)‐1,3,4‐oxadiazole 140 which were showing herbicidal activity. Compound 139 were found phytotoxicity against lettuce ( Lactuca sativa ) and bentgrass ( Agrostis stolonifera ) at 1 mM and compound 140 found the bleaching effect phenomenon against bentgrass at 1 mM.
…”
Section: Applications Of 134‐oxadiazolesmentioning
confidence: 99%
“…1,3,4-Oxadiazole, an important heterocyclic active fragment with significant pesticide biological activity, has attracted more and more attention of researchers for a long time [16][17][18][19][20][21]. Meanwhile, the previously studies had demonstrated that thioether derivatives had a broad spectrum of pesticide biological properties including antibacterial, antifungal, antiviral, and insecticidal activity [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%